UTILIZATION OF CLINICAL AND MEDICAL LABORATORY PARAMETERS AS INDICATORS OF MORTALITY IN INPATIENT BURNT CASES IN SULAIMANIYAH HOSPITAL FOR BURN AND PLASTIC SURGERY - Abdilkarim, Dana Abdilmagid (Journal of Sulaimani Medical College, 2024)
Background Burn injury is a complex traumatic event with a variety of local and systemic consequences that can be challenging to manage. Objectives To utilize clinical and laboratory parameter changes in the prediction of mortality of burn inpatients. Patients and Methods A retrospective study was conducted to assess clinical and laboratory parameter changes among children and adult burnt patients admitted to Burn & Plastic Surgery Hospital/Emergency. The study included two hundred fi fty-fi ve (255) deceased patients from December 2020 through February 2023. Result The female to male ratio was (3:1), more than half (58.7%) of cases had mixed 2nd and 3rd degree, and (31.1%) of cases had 3rd degree burn, while 2nd degree burns account for (10.2%). Flame was the most common cause of burns in most of the patients. The majority of the cases had an inhalational injury. The majority of the deceased patients (69.9%) had TBSA greater than 60%. Most of the patients were married and lived in major urban cities. Laboratory analysis of most of the dead had shown decreased total White Blood Cell count, red blood cell count, lymphocyte count, hemoglobin level, hematocrit, potassium/sodium, and total protein/albumin level. The platelet level was average. The majority of the cases the labratory results of Serum Chloride, Urea, Creatinin, and Glucose were increased. Conclusion and Recommendations Directing attention to these clinical and laboratory parameters is required to reduce mortality and improve patient survival.
Keywords: Laboratory parameter; Risk Factors; Burns; Mortality